Penerapan Metode Kontrol Proporsional Integral Pada Penghangat Makanan - Rohim, Abd; Pambudi, Wahyu Setyo (STMIK Budi Darma, 2021)
The application of control technology can be carried out in various fields, one of which is temperature control. This research process uses the PI control method, which is used to warm food at a temperature of 40-60°C. The sensor provides input to the ATmega16 Microcontroller. It issues an output in the form of the desired temperature for the food to activate the heater as a tool that will give the temperature that has been set by the control PI, read by the LM35 sensor and provides the temperature for ready-to-eat fried chicken with a temperature that has been established—controlled by the microcontroller. With proportional and integral values of P = 1.899999 and I = 0.999999, you can find out the time the temperature response graph rises or is called Rise Time RS = 1s, the stability time at the setpoint of 45°C is called Settling Time, ST = 4s, and the Steady Stade Error at the initial start and the average error that has been obtained is 35%. The percentage of stability at the set point of 45°C is 11%.